Responsiveness of clinical tests for people with neck pain - René Jørgensen (BMC Musculoskeletal Disorders, 2017)
Abstract Background Responsiveness of a clinical test is highly relevant in order to evaluate the effect of a given intervention. However, the responsiveness of clinical tests for people with neck pain has not been adequately evaluated. The objective of the present study was to examine the responsiveness of four clinical tests which are low cost and easy to perform in a clinical setting, including the craniocervical flexion test, cervical active range of movement, test for the cervical extensors and pressure pain threshold testing. Methods This study is a secondary analysis of data collected in a previously published randomised controlled trial. Participants were randomized to either physical training, exercises and pain education combined or pain education only. Participants were tested on the clinical tests at baseline and at 4-month follow-up. An anchor-based approach using Receiver Operator Characteristics (ROC) curves was used to evaluate responsiveness of the clinical tests. The Neck Disability Index was used to discriminate between those who had improved and those who were unchanged at the 4-month follow-up. Minimum Clinically Important Difference (MCID), together with sensitivity, specificity, positive and negative predictive values, in addition to positive and negative likelihood ratios were calculated. Results In total, 164 participants completed the 4 month follow up. One-hundred forty four participants were classified as unchanged whereas 20 patients were considered to be improved. Twenty-six participants didn’t complete all of the clinical tests, leaving a total of 138 to be included for analyses. Area Under Curve (AUC) ranged from 0.50-0.62 for the clinical tests, and were all below an acceptable level. MCID was generally large, and the corresponding sensitivity and specificity was low with sensitivity ranging from 20 to 60%, and specificity from 54 to 86%. LR+ (0.8-2.07) and LR- (0.7-1.1) showed low diagnostic value for all variables, with PPV ranging from 12.1 to 26.1 and NPV ranging from 84.7 to 89.2. Conclusion Responsiveness of the included clinical tests was generally low when using change in NDI score as the anchor from baseline to the 4-month follow up. Further investigations of responsiveness are warranted, possibly using other anchors, which to a higher degree resemble similar dimensions as the clinical tests.